The I-BATARA Learning Model: A Conceptual Framework Integrating Inquiry, Scaffolding, and Local Wisdom to Foster Scientific Literacy - Wiwin Puspita Hadi; Erman Erman; Suyatno Sutoyo (International Journal of Emerging Research and Review, 2026)
Objective: Scientific literacy, a foundational literacy, is essential for students to develop from an early age to prepare them for addressing the challenges of the global era. Therefore, effective instructional interventions are required to facilitate students' transition from concrete to abstract thinking by employing meaningful real-world contexts.  This research tries to formulate the I-BATARA learning model to increase the student’s scientific literacy. Method: This study employed a conceptual model development approach to construct the I-BATARA learning model. Results: The results indicate that the proposed I-BATARA instructional model integrates Inquiry-Based Learning, process-oriented scaffolding, and the authentic context of batik tulis Tanjung Bumi Madura into a coherent instructional framework designed to enhance students' scientific literacy. Novelty: The I-BATARA learning model its comprehensive integration of Inquiry-Based Learning (IBL), scaffolding, local wisdom, and scientific literacy instructional framework.